1973
DOI: 10.1111/j.1699-0463.1973.tb02250.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Blocking Serum Factors in Organ Grafted Rats

Abstract: The aim of the present study was to investigate whether inhibition of the mixed lymphocyte culture (M.L.C.) interaction by sera from organ transplanted rats could be used as an indicator of the development of immunological enhancement. The findings may be summarized as follows: 1) Conventionally produced immune sera exhibited an antigen‐specific inhibition of M.L.C. whether directed against the stimulating or the responding cells. 2) Sera from organ transplanted rats also consistently inhibited the M.L.C. inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1975
1975
1975
1975

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Sengar et al (1973) suggested a correlation between the presence of MLC blocking factor and long-term renal allograft survival in humans. However, Heron & Ssrensen (1973) observed no difference in the MLC inhibitory capacity of sera obtained either from rats who had rejected their grafts or from recipients of long-term surviving allografts. I n the present investigation, the MLC blocking system failed to distinguish between the action of plasma from recipients who had rejected the allo-grafts and from recipients showing longterm allograft acceptance.…”
Section: Discussionmentioning
confidence: 68%
“…Sengar et al (1973) suggested a correlation between the presence of MLC blocking factor and long-term renal allograft survival in humans. However, Heron & Ssrensen (1973) observed no difference in the MLC inhibitory capacity of sera obtained either from rats who had rejected their grafts or from recipients of long-term surviving allografts. I n the present investigation, the MLC blocking system failed to distinguish between the action of plasma from recipients who had rejected the allo-grafts and from recipients showing longterm allograft acceptance.…”
Section: Discussionmentioning
confidence: 68%